Terrestrial gamma dose rate mapping (Euganean Hills, Italy): comparison between field measurements and HPGe gamma spectrometric data. Issue 1 (2nd January 2020) - Cinelli, G.; Brattich, E.; Coletti, C.; De Ingeniis, V.; Mazzoli, C.; Mostacci, D.; Sassi, R.; Tositti, L.
Abstract : Terrestrial gamma radiation is mostly due to radionuclides in soil and rocks, primarily the 238 U, 235 U and 232 Th radioactive families and 40 K. This radiation contributes 15% to public exposure from all ionizing radiation sources, considering global population. Moreover, it can be used to estimate radon flux and included as one of the quantities relevant to the geogenic radon hazard model. Therefore, effort has been put into developing maps of terrestrial gamma dose rate at the regional, national or European scale, using different input data and methods. In the present work, two distinct approaches to map terrestrial gamma dose rate have been tested in the Euganean Hills district of NE Italy. The first one is based on 41 in situ measurements of ambient dose equivalent rates using a rate meter equipped with a NaI scintillator probe. The second one estimates terrestrial gamma dose rate from the U, Th and K activity concentrations in rock samples collected at the same locations of the dose rates measurements. The results obtained indicate good agreement between the two approaches, and as such suggest that the UNSCEAR 2008 prescription to derive ambient dose equivalent rate from laboratory gamma measurements produces reliable data, provided that cosmic and fall-out contributions are included. Moreover, the study proved that mapping the ambient dose equivalent rate (or terrestrial gamma dose rate) using only one database – i.e. either measured data or estimates derived from radionuclide activity concentration – yields valid results.